La mer, miroir de la légitimité du califat nasride. À propos du Khaṭrat al-ṭayf d’Ibn al-Khaṭîb (1347) - Yann Dejugnat (Revue des Mondes Musulmans et de la Méditerranée)
The Khaṭrat al-ṭayf fî riḥlat al-shitâ’ wa-l-ṣayf of Ibn al-Khaṭîb (1347) is a work which was widely neglected by most of the studies dedicated to the genre of the account of travel (riḥla). The objective of this article is to make appear, by the approach of this narrative as a speech, the meaning in the Nasrid Kingdom of Granada. As announces it the title which is a quotation of the sura CVI of the Koran, Ibn al-Khaṭîb proceeded to a coranisation of the riḥla by likening the official procession of the sovereign Yûsuf I between Granada and Almeria to the route of the caravans of Quraysh between Mecca and Ṭâ’if. Establishing a mirror effect between both peninsulas, Arabian and Iberic, and taking up with the origins of Islam, the travel was conceived as an instrument of legitimization. In this symbolic construction, the sea appears as the privileged space to express the caliphal ambitions and the hopes of revenge on the Christians of the nasrid power.